Effect of pre-operative radiation therapy on surgical outcome in retroperitoneal sarcoma - Jo, Sung Jun; Park, Sean S. W.; Yoo, Gyu Sang; Kim, Kyeong Deok; Lim, So Hee; Kim, Jinseob; Kim, Min Jung; Yu, Jeong Il; Park, Jae Berm; Lee, Kyo Won (Frontiers in Surgery, 2023)
Background: A high rate of locoregional recurrence is one of the major difficulties in successful treatment of retroperitoneal sarcoma (RPS). Although pre-operative radiation therapy (RT) is considered a potential way to improve local recurrence, concerns about the associated treatment toxicity and risk of peri-operative complications need to be addressed. Hence, this study investigates the safety of pre-operative RT (preRTx) for RPS. Methods: A cohort of 198 patients with RPS who had undergone both surgery and RT was analyzed for peri-operative complications. They were divided into three groups according to the RT scheme: 1) preRTx group, 2) post-operative RT without tissue expander, and 3) post-operative RT with tissue expander. Results: The preRTx was overall well tolerated and did not affect the R2 resection rate, operative time, and severe post-operative complications. However, the preRTx group was associated with higher incidence of post-operative transfusion and admission to intensive care unit (p = 0.013 and p = 0.036, respectively), where preRTx was an independent risk factor only for the post-operative transfusion (p = 0.009) in multivariate analysis. The median radiation dose was the highest in preRTx group, although no significant difference was demonstrated in overall survival and local recurrence rate. Conclusion: This study suggests that the preRTx does not add significant post-operative morbidity to the patients with RPS. In addition, radiation dose elevation is achievable with the pre-operative RT. However, a meticulous intra-operative bleeding control is recommended in those patients, and further high-quality trials are warranted to evaluate the long-term oncological outcomes.